2017
DOI: 10.1002/jat.3575
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor‐based bioassays for dioxin detection: Thinking outside the box

Abstract: Despite intensive media coverage and international regulations, man-made persistent organic pollutants such as dioxins represent a serious environmental and health threat. Their detection by sophisticated chromatography technologies is highly complex, impeding the constant monitoring of food or environmental samples. This limitation has fostered the development of generations of bioassays exploiting the molecular function of the aryl hydrocarbon receptor (AhR), which binds toxic compounds and directly activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…Thus, the quantification of AHR agonists is of clinical interest. Multiple in vivo and in vitro bioassays exist to quantify AHR agonistic activity in biological samples 30 . Denison and colleagues developed reporter systems based on constructs in which the expression of the firefly luciferase gene is driven by XREs present in the promoter of Cyp1a1 , a metabolic gene under control of AHR 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the quantification of AHR agonists is of clinical interest. Multiple in vivo and in vitro bioassays exist to quantify AHR agonistic activity in biological samples 30 . Denison and colleagues developed reporter systems based on constructs in which the expression of the firefly luciferase gene is driven by XREs present in the promoter of Cyp1a1 , a metabolic gene under control of AHR 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory animals, they are known to give rise to weight loss, reproductive toxicity, developmental toxicity, tumorigenesis, and immune system dysfunction. 93 Endocrine actions are thought to be largely mediated through aryl hydrocarbon receptor (AhR)-mediated mechanisms, 93 , 94 but there are also defined estrogen antagonist activities mediated through cross-talk between estrogen receptor and AhR pathways. 94 Clinical studies have reported detrimental effects on human semen quality.…”
Section: Sources Of Exposure To Edcs In Airmentioning
confidence: 99%
“…PAHs have a known toxicity profile and many are genotoxic/carcinogenic. 100 Their carcinogenicity is thought to result from the ability of some PAHs to form reactive diol epoxide intermediates catalyzed by cytochrome P450 (CYP) enzymes (which may be induced themselves by PAHs through an AhR-mediated mechanism 93 , 94 ) and then the subsequent covalent binding of these intermediates to DNA. Carcinogenicity of other PAHs may originate from their ability to generate reactive oxygen species resulting in oxidative stress and inflammatory responses.…”
Section: Sources Of Exposure To Edcs In Airmentioning
confidence: 99%
“…AhR-based bioassays can be classified into two categories by the AhR sources: endogenous AhR-based and exogenous AhR-based . Ethoxyresorufin- O -demethylase (EROD) assay and chemically activated luciferase expression (CALUX) are two of the most widely used methods for detecting dioxin-like compounds.…”
Section: Sampling and Analysismentioning
confidence: 99%
“…The utilization of exogenous AhR molecules is uncommon in the detection of dioxin. However, it will be a promising method for the development of techniques in cloning and manipulation of AhR …”
Section: Sampling and Analysismentioning
confidence: 99%